Serum Biochemical and Meat Fatty Acid Profiles of Different Chicken Genotypes - Hailemariam, A.; Esatu, Wondmeneh; Abegaz, Solomon; Urge, Mengistu; Assefa, Getnet; Dessie, Tadelle (Scientific Research Publishing, Inc., 2022)
Serum biochemical and meat fatty acid profile of different chickens were studied. A total of 144 mixed sex matured chickens of Cosmopolitan (C), Improved Horro (H), Cosmopolitan♂*Improved Horro♀(CH), Improved Horro♂*Cosmopolitan♀ (HC), Indigenous (L) and Koekkoek (KK) were used to determine serum biochemical, of which 36 chickens were also used for fatty acid profile study. Completely randomized design in 6 × 2 factorial arrangements was set up. Serum biochemical and fatty acid profiles were determined by Roche/Hitachi cobas c 501 and gas liquid chromatography (GC) procedures, respectively. There were significant differences (P ≤ 0.001) in Total cholesterol (TC), Triglyceride (TG), Low-density lipoprotein (LDL) and High-density lipoprotein (HDL) among genotypes and between sexes. HDL was inversely related with TC, TG and LDL. Male had significantly higher (P ≤ 0.001) TC, TG, LDL but lower HDL than female. SFA, (Myristic, Pentadecanoic and Palmitic acids) had significantly (P < 0.05) varied among genotypes. However, Margaric (P ≤ 0.01) and stearic (P ≤ 0.001) acids were significantly different between sexes. Myristoleic and Palmitoleic acids significantly vary (P ≤ 0.05) among genotypes and between sexes. Oleic (P ≤ 0.01) and Eicosenoic (P ≤ 0.001) significantly influenced by sex. Moreover, Linoleic had significantly (P ≤ 0.01) affected by genotypes. Nevertheless, α-linolenic acid significantly (P ≤ 0.01) varied between sexes. The serum biochemical differed across genotypes and between sexes. The difference in the number of carbons, double bond and position of the double bond could affect fatty acid profile among genotypes and between sexes. Chicken products with higher level TC, TG, LDL and SFA might affect human health problems. It could also be interesting topic for future studies.